Sleep Quality and Duration Associations with Metabolic Health Markers - Nur Ainnah Mulyadi (Journal of Nutrition and Health Care, 2025)
Sleep disturbances have become an increasingly common public health issue in modern society, with potentially significant metabolic consequences. This study aimed to investigate the relationship between sleep quality and duration with key metabolic health markers. In this cross-sectional observational study, data from 1,250 adult participants (aged 25-65 years) were collected using a combination of polysomnography, Pittsburgh Sleep Quality Index (PSQI) questionnaires, and anthropometric and biochemical measurements. Parameters assessed included fasting blood glucose, lipid profiles, insulin sensitivity, inflammatory markers, and indicators of body composition. Results revealed significant inverse correlations between sleep duration and fasting blood glucose levels (p<0.001), insulin resistance (p<0.001), and inflammatory markers including CRP (p<0.01). Additionally, poor sleep quality was independently associated with unfavorable lipid profiles, including elevated triglycerides (p<0.01) and reduced HDL (p<0.05), after adjusting for potential confounding factors such as age, gender, and body mass index. Subgroup analyses revealed that sleep effects on metabolic parameters were more pronounced in individuals with higher body mass indices and those with pre-existing metabolic syndrome. These findings affirm the importance of adequate sleep patterns in maintaining metabolic homeostasis and suggest that interventions targeting sleep improvement may have therapeutic applications in the management of metabolic disorders.